A bio-sensing surface with high biocompatibility for enhancing Raman scattering signals as enabled by a Mo–Ag film. Issue 7 (2nd March 2022) - Chen, Dongzhen; Li, Yang; Wang, Lijun; Wang, Yingjie; Ning, Pan; Shum, Powan; He, Xinhai; Fu, Tao
Abstract : The sensitive SERS sensing of molecules and bacteria was acquired through a Mo–Ag film with high cytocompatibility and hydrophilicity. Abstract : Biological surface-enhanced Raman scattering (SERS) sensing is dependent on the properties of the sensing surface. For the biological sensing surfaces for SERS, the hydrophilicity, biocompatibility and signal sensitivity are pivotal. Hence, a hard bimetallic Mo–Ag film was developed by a magnetron sputtering technique, and the surface morphology could be controlled by the relative contents of Mo and Ag. The Mo–Ag film has better hydrophilicity than the pure Ag film, which could be beneficial for cell attachment during biological SERS sensing. Moreover, the cell test shows that the Mo–Ag film exhibits good cytocompatibility with MC3T3-E1 cells, which shows potential for SERS detection in vivo . The high surface roughness of the Mo–Ag film is a fascinating feature for enhancing Raman scattering signals. Through depositing a thin film of Mo–Ag on a glass surface with a size of 0.5 × 0.5 cm 2, a sensing chip of SERS could be produced. High sensitivity and excellent signal reproducibility were acquired. The sensitivity was down to 10 −10 mol L −1 for malachite green and 10 −9 mol L −1 for thiram, and the relative standard deviation value was lower than 7.0%. Moreover, bacteria were detected by employing the Mo–Ag film chip, and the difference in signal uniformity between molecules and bacteria is illustrated. In summary, depositing the Mo–Ag film on the surface of sensors could be an effective strategy for biomedical SERS sensing.